Pembentukan Hidroksikarbonat Apatit Oleh Pasta Injeksi Bioactive Glass Berbasis Silika Abu Ampas Tebu Dan Penambahan Karageenan Rumput Laut - Didin Erma Indahyani; Izzata Barid; Riris Aria Dewanti (Fakultas Kedokteran Gigi Universitas Jember, 2023)
Root caries is common in the elderly, usually detected late, involving enamel, cementum, and dentin below the cementoenamel junction (CEJ). Remineralisation is used to treat it when cavitation has not occurred. Bioactive glass triggers remineralisation by forming hydroxycarbonate apatite (HCA) at an early stage. Injectable paste preparations are needed to overcome these problems. The use of hyaluronic acid and carrageenan polymers supports the physical and mechanical properties of the paste preparation. The purpose this research to analyse the formation of HCA on the tooth root surface by administering bioactive glass (BAG) injection paste with the addition of seaweed carrageenan. This study was a laboratory experimental study with three research groups, namely treatment group 1 (BAG paste and hyaluronic acid), treatment 2 (BAG paste, hyaluronic acid and carrageenan), and control group (BAG without polymer). All groups were immersed in artificial saliva, incubated at 37oC for six days and then tested by Scanning Electron Microscope (SEM) to see the formation of HCA and FTIR. HCA was quantified by a scoring method according to predetermined score criteria. SEM showed HCA formation in both treatment groups, not the control group. There is HCA formation on the tooth surface by administering BAG injection paste with seaweed carrageenan.